Intimate Partner Violence Before Pregnancy, During Pregnancy, and After Childbirth: A New Conceptualization Highlighting Individual Changes in Violence Against Pregnant Women Over Time. Issue 13 (July 2022) - Chan, Ko Ling; Lo, C. K. M.; Lu, Y.; Ho, Frederick K.; Leung, Wing Cheong; Ip, Patrick
Intimate partner violence (IPV) against pregnant women is a global public health problem. Yet, the trajectory of IPV during pregnancy and its association with health are unclear. This study set out to investigate the trajectory of IPV by categorizing pregnant women according to changes of IPV exposure before, during, and after pregnancy and to examine the predictive factors of these IPV-related categories. During 2016 and 2017, we conducted a longitudinal study with a sample of 1, 083 pregnant women in Hong Kong. Pregnant women reported their IPV experiences, depression, and demographics in the baseline survey (at about 24-week gestation), and their IPV experiences, mental health outcomes, social support, and perceived father's involvement in the follow-up survey (around 4 weeks postpartum). We categorized pregnant women into four groups, including women with (a) sustaining abusive relationship (AR); (b) relationship with decreased violence over pregnancy (DVR); (c) relationship with stress-related violence (SVR); and (d) nonviolent relationship (NVR). Although we found an overall decline of IPV during pregnancy from 24.6% to 14.3%, there were still a considerable proportion of women reporting as a victim of IPV. We observed that a higher proportion of pregnant women were actually suffering from IPV during pregnancy and after childbirth continuously (22.3% of AR and SVR) than experiencing a termination of IPV due to pregnancy (11.4% of DVR). We also observed that more severe maternal depression, lower levels of father's involvement, and poorer social support were significantly associated with the categories that reflected greater severity of IPV over the course of pregnancy. Our findings reflected that the complexity of IPV related to pregnancy should never be overlooked. Mere reporting of prevalence in an aggregate might not sufficiently explain the problem. Father's involvement and social support are two important factors that might help reduce IPV related to pregnancy and childbirth.